The Role of HIV Research in Building Health System Capacity in Developing Countries - Zewdie, Debrework; Cahn, Pedro; McClure, Craig; Bataringaya, Jacqueline (Current Opinion in HIV and AIDS, 2008)
There is growing recognition that greater investment in research is needed to expand our knowledge and understanding of how to scale up HIV programmes effectively and equitably in the context of weak health systems. Current debates acknowledge that there remains a gap in evidence on how HIV resources can best be managed to contribute to building health system capacity; how to integrate HIV interventions into primary healthcare systems; and how HIV scale-up is affecting other disease programmes.
Keywords: HIV; Research; Health system capacity